2020
DOI: 10.1016/j.heliyon.2020.e05579
|View full text |Cite
|
Sign up to set email alerts
|

Proconvulsant effects of Nepeta menthoides hydro alcoholic extract in different seizure tests: behavioral and biochemical studies

Abstract: In Iran, both Nepeta menthoides-the endemic species of Nepeta genus-and Lavandula officinalis are known as Ustukhuddoos and used widely as medicinal herbs. In Iranian traditional medicine, Ustukhuddoos has been recommended for several neuronal diseases including depression and epilepsy. While the antiepileptic effects of Lavandula officinalis have been investigated in a number of studies, no reports are available taking into account the effect of Nepeta menthoides on epilepsy. Since convulsion is an important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The rough eye phenotype (REP), which is induced by A42, is one way in which the severity of neurotoxicity and the presence of Alzheimer's disease can be determined [105]. The results of the inquiry into REP suggested that flies fed with limonene had eased REP in a manner that was comparable to that of donepezil, which had been employed as the positive control because it was likewise effective in relieving REP. Limonene was shown to have anti-inflammatory properties when it was examined, and the results showed a significant reduction in the number of activated glial cells and nitric oxide (NO) expression in the heads of flies that were treated with limonene [106].…”
Section: Citrus Plantmentioning
confidence: 99%
“…The rough eye phenotype (REP), which is induced by A42, is one way in which the severity of neurotoxicity and the presence of Alzheimer's disease can be determined [105]. The results of the inquiry into REP suggested that flies fed with limonene had eased REP in a manner that was comparable to that of donepezil, which had been employed as the positive control because it was likewise effective in relieving REP. Limonene was shown to have anti-inflammatory properties when it was examined, and the results showed a significant reduction in the number of activated glial cells and nitric oxide (NO) expression in the heads of flies that were treated with limonene [106].…”
Section: Citrus Plantmentioning
confidence: 99%
“…and intraperitoneal (i.p.) injection of PTZ models in our current work, which have been utilized widely as the lab assessments to evaluate the anti-seizure effects of medication and to develop new antiepileptic therapies [ 40 , 41 , 42 , 43 , 44 ]. Similarly, the maximal electroshock-induced tonic-clonic seizure is the most severe electroshock convulsive response induced by supramaximal electrical stimulation currents.…”
Section: Introductionmentioning
confidence: 99%